PRINCIPAL AS A MANAGER IN IMPROVING THE QUALITY OF EDUCATION - Enur Rohmah (Managere: Indonesian Journal of Educational Management, 2021)
This study aims to analyze and understand the role of madrasah principals as managers in improving the quality of education of Islamic elementary schools in Cililin District, West Bandung Regency. This research uses a qualitative case study approach. The data was collected through interviews, observations, and documentation. The data analysis is carried out in stages: data presentation, data reduction, and concluding. The results showed that the role of the madrasah principal as a manager in improving the quality of education was manifested in the planning of a systematic and measurable work program involving all components of the madrasa, the use of an effective and efficient situational leadership system, to be able to mobilize his subordinates to realize the school's vision and mission and display a communication style that is by the culture of the character of his associates.